Differential Response to Low-Dose Dopamine or Low-Dose Nesiritide in Acute Heart Failure with Reduced or Preserved Ejection Fraction: Results from the Renal Optimization Strategies Evaluation in Acute Heart Failure (ROSE AHF) - Wan, Siu-Hin (Circ Heart Fail, 2016)
BACKGROUND: The Renal Optimization Strategies Evaluation in Acute Heart Failure (ROSE AHF) trial found that as compared to placebo, neither low-dose dopamine (2 ug/kg/min) nor low-dose nesiritide (0.005 µg/kg/min without bolus) enhanced decongestion or preserved renal function in AHF patients with renal dysfunction. However, there may be differential responses to vasoactive agents in AHF patients with reduced versus preserved ejection fraction (EF). This post-hoc analysis examined potential interaction between treatment effect and EF group (EF ≤ 40% vs > 40%) on the ROSE AHF endpoints. METHODS AND RESULTS: ROSE AHF enrolled AHF patients (n=360; any EF) with renal dysfunction. The co-primary endpoints were cumulative urine volume and the change in serum cystatin-C from over 72 hours. The effect of dopamine (interaction p=0.001) and nesiritide (interaction p=0.039) on urine volume varied by EF group. In HFrEF, urine volume was higher with active treatment versus placebo whereas in HFpEF, urine volume was lower with active treatment. The effect of dopamine and nesiritide on weight change, sodium excretion and incidence of AHF treatment failure also varied and in a similar manner by EF group (interaction p<0.05 for all). There was no interaction between either vasoactive treatment’s effect and EF group on change in cystatin-C. Compared to placebo, dopamine was associated with improved clinical outcomes in HFrEF and worse clinical outcomes in HFpEF. With nesiritide, there were no differences in clinical outcomes as compared to placebo in both HFrEF and HFpEF. CONCLUSIONS: In this post-hoc analysis of ROSE AHF, the response to vasoactive therapies differed in patients with HFrEF and HFpEF. Investigation of AHF therapies should assess the potential for differential responses in AHF with preserved versus reduced EF. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01132846.